Social models of anti-corruption and corrupt practices in the global and European dimension - Chumachenko, Denys (2021)
The article presents a comparative (comparative) analysis of social models of anti-corruption and corrupt practices in the global and European dimensions. The basic models of anti-corruption are identified and analysed: the first model, vertical, where the impact on the spread of corruption and corrupt practices is carried out vertically, which is based mainly on repressive (harassment, criminal liability) mechanisms, strict legal sanctions and social control; the second model is horizontal (model of systemic elimination of corruption factors), which provides for the use of repressive methods, social control and preventive mechanisms related to public involvement, formation of "anti-corruption" imperatives in society, high level of legal culture and social responsibility based on democratic principles structure of social life.